Effect of Rehabilitation Training for Pregnancy Outcomes and Postpartum Quality of Life in Thyroid Cancer Survivors: A Propensity Score-Matched Cohort Study - Xiaoxia Zhou; Wanshu Zhu; Yueqing Xue; Cuihui Chen; Wei Chen; Miaoli Zhou (IMR Press, 2024)
Background: This retrospective cohort study aimed to evaluate the impact of exercise intervention, specifically combined aerobic and resistance training, on the quality of life, mental health, and pregnancy outcomes of women with a history of treated papillary thyroid cancer, particularly those who underwent radioactive iodine therapy. Methods: The study is a propensity score-matched cohort study. The cohort was divided into observation and controls based on the presence or absence of thyroid cancer history and adherence to exercise intervention. Propensity score matching was employed for comparable group creation. Exercise interventions were initiated between the 16th and 20th week of gestation, lasting at least 16 weeks. Baseline information, thyroid function, maternal outcomes, neonatal outcomes, and quality of life were assessed. Statistical analyses included subgroup analyses based on age. Results: A total of 4432 women were initially included, with 84 in the observation group and 3114 in the control group after exclusions. Following post-matching, a total of 252 participants contributed data to our study. However, post-intervention observations revealed that participants exhibited elevated anxiety levels (45.81 ± 10.66 vs. 39.72 ± 12.79, p = 0.006), along with decreased placental weight (562.10 ± 64.45 vs. 581.02 ± 65.20, p = 0.007). Older mothers (>35 years) in the survivor group showed a higher risk of anemia (p = 0.005), subgroup analysis revealed significant differences in the incidence of anemia among older mothers. Conclusions: Exercise intervention, specifically combined aerobic and resistance training, is considered safe for pregnant women with treated papillary thyroid cancer, enhancing pregnancy status without adversely affecting outcomes. While anxiety levels may persist postpartum, exercise interventions do not worsen pregnancy outcomes. Attention is warranted for the increased risk of anemia in older mothers following exercise intervention. Despite limitations, this study contributes valuable insights for the care of thyroid cancer survivors during pregnancy.